Entrepreneurial Marketing: A Panacea for Market Performance of Small-Sized Enterprises (SSEs) in Benin City, Nigeria - Eleazar Chibuzor Gbandi; Uwaraye Patience Oware (Faculty of Economics, Universitas Sriwijaya, 2022)
AbstractThe study looked at the impact of entrepreneurial dimensions and market performance of small sized-enterprises in Benin City, Edo State, Nigeria. Two hundred and forty two (242) respondents who are owners or managers of SSEs in the Benin City Metropolis were selected as the sample size of the study using stratify and random sampling techniques. Data from respondents were gathered using a survey research design and a questionnaire. Multiple regressions were used to analyse the relationship between the study's variables that had been hypothesized. Results show a substantial positive and significant association between the entrepreneurial marketing dimensions (pro-activeness, opportunity-focus, innovation-oriented, customer focus, resource leveraging, and value creation) and market performance of SSEs in Benin City, Edo State, Nigeria. As a result, the study recommends that SSEs should use aggressive entrepreneurial marketing dimensions to enhance their market performance in terms of sales expansion and profitability.